2020
DOI: 10.3390/toxins12050329
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Stress Induction of the Mycobacterium tuberculosis MbcTA Bactericidal Toxin-Antitoxin System

Abstract: MbcTA is a type II toxin/antitoxin (TA) system of Mycobacterium tuberculosis. The MbcT toxin triggers mycobacterial cell death in vitro and in vivo through the phosphorolysis of the essential metabolite NAD+ and its bactericidal activity is neutralized by physical interaction with its cognate antitoxin MbcA. Therefore, the MbcTA system appears as a promising target for the development of novel therapies against tuberculosis, through the identification of compounds able to antagonize or destabilize the MbcA ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 41 publications
1
10
0
Order By: Relevance
“…Therefore, reducing the intracellular level of NAD + by ResA might rewire the cell metabolism and interfere with the redox homeostasis, which might contribute to increased antibiotic tolerance. A recent study demonstrated that overexpression of a M. tuberculosis toxin MbcT in Mycobacterium smegmatis depleted the intracellular NAD+ and lead to cell death [ 51 ]. We suspect that ResA might display obvious growth inhibitory effects under certain environmental stresses such as carbon or amino acid starvation.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, reducing the intracellular level of NAD + by ResA might rewire the cell metabolism and interfere with the redox homeostasis, which might contribute to increased antibiotic tolerance. A recent study demonstrated that overexpression of a M. tuberculosis toxin MbcT in Mycobacterium smegmatis depleted the intracellular NAD+ and lead to cell death [ 51 ]. We suspect that ResA might display obvious growth inhibitory effects under certain environmental stresses such as carbon or amino acid starvation.…”
Section: Discussionmentioning
confidence: 99%
“…M. tuberculosis encodes an unusually high number of TA systems, over 86, representing close to 4% of its genome (Akarsu et al , 2019; Sala et al , 2014). This includes multiple homologs from conserved TA families that have been shown to be induced under relevant stress conditions, including hypoxia, macrophage engulfment, or drug exposure (Ramage et al , 2009; Keren et al , 2011; Ariyachaokun et al , 2020). Although their contribution to M. tuberculosis physiology and virulence is currently unknown, it has been proposed that activated toxins could modulate M. tuberculosis growth under certain conditions, thereby contributing to survival in the human host (Keren et al , 2011; Barth et al , 2021; Sala et al , 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some members have recently been implicated in solvent tolerance, plasmid stability or stress-mediated growth inhibition 12,14,[20][21][22] . E.g., the MbcA-MbcT system of M. tuberculosis is significantly upregulated in a variety of stress conditions, including persister cells 23 , hypoxic stress 24 , starvation 25 , and in human macrophages 26,27 . Similarly, the natR-natT module of P. aeruginosa is induced under oxidative stress conditions, exposure to antibiotics and under host-like conditions [28][29][30] and natT mutants show reduced survival during antibiotic treatment and in macrophages 30 .…”
Section: Introductionmentioning
confidence: 99%